ANALISIS PERUBAHAN HUTAN MANGROVE MENGGUNAKAN CITRA LANDSAT - Haryani, Nanik Suryo (Lembaga Layanan Pendidikan Tinggi Wilayah III Jakarta, 2013)
Indonesia is a country of the largest mangrove forest in the world, but the deforestation problem will lead into the change of coastal ecosystem which causes the downgrade the physical, biological and economic level. The goal of this research is to analyze the change of mangrove forest using the Landsat image of 2001–2011 in Probolinggo Regency. Based on the result of analysis of Landsat image of 2001 and 2011, it is indicated that during 11 years period there is a change of mangrove forest area, with the most dominant change happened in Tambakrejo village at 25,57 hectars, in Lemahkembar village at 22,46 hectars and in Mangunharjo village at 17,66 hectars. Meanwhile, the less dominant change of mangrove forest was happened in Sumberanyar village at 3,25 hectars, Bayeman village at 1,82 hectars, and Dungun village at 1,31 hectars.